Exploring Students’ Experiences in Essay Writing Learning through YouTube Channel Engagement - Azizah, Roja Nur; Saadillah, Saadillah; Mufidah, Nida (English Department of Faculty of Tarbiyah and Teacher Training, 2025)
This study investigates EFL students' experiences using YouTube channels in their essay-writing learning. Ten fourth-semester English Education Department students from UIN Antasari Banjarmasin participated in the study. Interviews and documentation were used to gather data using a qualitative approach and the narrative inquiry method. The results indicated that YouTube videos provide visual aids and flexible access, which aid students in developing their writing abilities, increasing their vocabulary, and learning on their own. Nevertheless, problems including passive learning, distraction, and a lack of lecturer contact also surfaced. In general, YouTube's contribution to writing education was seen as advantageous.